Національна транспортна політика як умова економічної безпеки держави - Матвєєва, А. В. (Право, 2016)
The article identifies that one of the major signs of the present stage of the global economy is strengthening of integration processes. It causes the deepening of international labor division and international economic cooperation. Formation of global and regional labor markets, goods, capital and services are the result of such processes. This leads to the growth of transnational transportation and the international transit of goods. // У статті визначено, що однією з основних ознак сучасного етапу світової економіки є зміцнення інтеграційних процесів. Це викликає поглиблення міжнародного розподілу праці та міжнародне економічне співробітництво. Формування глобальних та регіональних ринків праці, товарів, капіталу та послуг є результатом таких процесів. Це призводить до зростання транснаціонального перевезення та міжнародного транзиту товарів.
The national transport policy as a condition of economic safety of the state
Keywords: transport policy; transport corridor; freight; legal regulation of national transport policy; транспортна політика; транспортні коридори; вантаж; правове регулювання національної транспортної політики